2025-01-12

945: Product Module

<The previous article in this series | The table of contents of this series | The next article in this series>

definition of product module

Topics


About: module

The table of contents of this article


Starting Context



Target Context


  • The reader will have a definition of product module.

Orientation


There is a list of definitions discussed so far in this site.

There is a list of propositions discussed so far in this site.


Main Body


1: Structured Description 1


Here is the rules of Structured Description.

Entities:
J: { the possibly uncountable index sets }
R: { the rings }
{Mj|jJ}: { the R modules }
×jJMj: = the product set , { the R modules }, with the operations specified below
//

Conditions:
rR,f×jJMj(jJ((rf)(j)=r(f(j))))

f,f×jJMj(jJ((f+f)(j)=f(j)+f(j)))
//


2: Structured Description 2


Here is the rules of Structured Description.

Entities:
R: { the rings }
{M1,...,Mk}: { the R modules }
M1×...×Mk: = the product set , { the R modules }, with the operations specified below
//

Conditions:
rR,m=(m1,...,mk)M1×...×Mk(rm=(rm1,...,rmk))

m=(m1,...,mk),m=(m1,...,mk)M1×...×Mk(m+m=(m1+m1,...,mk+mk))
//


3: Note


Let us see that ×jJMj is indeed an M module.

1) m,m×jJMj(m+m×jJMj) (closed-ness under addition): for each jJ, (m+m)(j)=m(j)+m(j)Mj.

2) m,m×jJMj(m+m=m+m) (commutativity of addition): for each jJ, (m+m)(j)=m(j)+m(j)=m(j)+m(j)=(m+m)(j).

3) m,m,m×jJMj((m+m)+m=m+(m+m)) (associativity of additions); for each jJ, ((m+m)+m)(j)=(m+m)(j)+m(j)=m(j)+m(j)+m(j)=m(j)+(m+m)(j)=(m+(m+m))(j).

4) 0×jJMj(m×jJMj(m+0=m)) (existence of 0 element): m0×jJMj such that for each jJ, m0(j)=0 is 0, because (m+m0)(j)=m(j)+m0(j)=m(j)+0=m(j).

5) m×jJMj(m×jJMj(m+m=0)) (existence of inverse element): m×jJMj such that for each jJ, m(j)=m(j) is such a one, because (m+m)(j)=m(j)+m(j)=m(j)+m(j)=0=m0(j).

6) m×jJMj,rR(r.m×jJMj) (closed-ness under scalar multiplication): for each jJ, (r.m)(j)=rm(j)Mj.

7) m×jJMj,r1,r2R((r1+r2).m=r1.m+r2.m) (scalar multiplication distributability for scalars addition): for each jJ, ((r1+r2).m)(j)=(r1+r2)m(j)=r1m(j)+r2m(j)=(r1m)(j)+(r2m)(j)=(r1.m+r2.m)(j)).

8) m,m×jJMj,rR(r.(m+m)=r.m+r.m) (scalar multiplication distributability for elements addition): for each jJ, (r.(m+m))(j)=r(m+m)(j)=r(m(j)+m(j))=rm(j)+rm(j)=(rm)(j)+(rm)(j)=(r.m+r.m)(j).

9) m×jJMj,r1,r2R((r1r2).m=r1.(r2.m)) (associativity of scalar multiplications): for each jJ, ((r1r2).m)(j)=(r1r2)m(j)=r1(r2m(j))=r1.(r2.m)(j).

10) m×jJMj(1.m=m) (identity of 1 multiplication): for each jJ, (1.m)(j)=1m(j)=m(j).

Let us see that M1×...×Mk is indeed an R module.

1) m,mM1×...×Mk(m+mM1×...×Mk) (closed-ness under addition): for m=(m1,...,mk) and m=(m1,...,mk), m+m=(m1,...,mk)+(m1,...,mk)=(m1+m1,...,mk+mk)M1×...×Mk.

2) m,mM1×...×Mk(m+m=m+m) (commutativity of addition): for m=(m1,...,mk) and m=(m1,...,mk), m+m=(m1,...,mk)+(m1,...,mk)=(m1+m1,...,mk+mk)=(m1+m1,...,mk+mk)=m+m.

3) m,m,mM1×...×Mk((m+m)+m=m+(m+m)) (associativity of additions); for m=(m1,...,mk), m=(m1,...,mk), and m=(m1,...,mk), (m+m)+m=(m1+m1,...,mk+mk)+(m1,...,mk)=(m1+m1+m1,...,mk+mk+mk)=m+(m1+m1,...,mk+mk)=m+(m+m).

4) 0M1×...×Mk(mM1×...×Mk(m+0=m)) (existence of 0 element): m0M1×...×Mk such that m0=(0,...,0) is 0, because for m=(m1,...,mk), m+m0=(m1,...,mk)+(0,...,0)=(m1+0,...,mk+0)=(m1,...,mk)=m.

5) mM1×...×Mk(mM1×...×Mk(m+m=0)) (existence of inverse element): mM1×...×Mk such that for m=(m1,...,mk), m=(m1,...,mk) is such a one, because m+m=(m1,...,mk)+(m1,...,mk)=(m1+m1,...,mk+mk)=(0,...,0)=m0.

6) mM1×...×Mk,rR(r.mM1×...×Mk) (closed-ness under scalar multiplication): for m=(m1,...,mk), r.m=(rm1,...,rmk)Mj.

7) mM1×...×Mk,r1,r2R((r1+r2).m=r1.m+r2.m) (scalar multiplication distributability for scalars addition): for m=(m1,...,mk), (r1+r2).m=((r1+r2)m1,...,(r1+r2)mk)=(r1m1+r2m1,...,r1mk+r2mk)=(r1m1,...,r1mk)+(r2m1,...,r2mk)=r1.m+r2.m).

8) m,mM1×...×Mk,rR(r.(m+m)=r.m+r.m) (scalar multiplication distributability for elements addition): for m=(m1,...,mk) and m=(m1,...,mk), r.(m+m)=r(m1+m1,...,mk+mk)=(r(m1+m1),...,r(mk+mk))=(rm1+rm1,...,rmk+rmk)=(rm1,...,rmk)+(rm1,...,rmk)=r.m+r.m.

9) mM1×...×Mk,r1,r2R((r1r2).m=r1.(r2.m)) (associativity of scalar multiplications): for m=(m1,...,mk), (r1r2).m=(r1r2)(m1,...,mk)=(r1r2m1,...,r1r2mk)=r1(r2m1,...,r2mk)=r1.(r2.m).

10) mM1×...×Mk(1.m=m) (identity of 1 multiplication): for m=(m1,...,mk), 1.m=1(m1,...,mk)=(1m1,...,1mk)=(m1,...,mk)=m.


References


<The previous article in this series | The table of contents of this series | The next article in this series>